2009
DOI: 10.1007/s12018-009-9052-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding on Bone Metabolism

Abstract: Bone metabolism responds to long-term energy balance, but is also regulated acutely by feeding. In vitro, animal and human studies have demonstrated complex effects of feeding on bone metabolism, which may be mediated through multiple interacting pathways. The most important mediators of the effects of feeding on bone metabolism are likely to be enteric and pancreatic hormones, such as incretins, amylin, preptin, pancreatic polypeptide, and peptide YY. These mediators may regulate bone turnover by direct effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Mechanistic evidence explaining the involvement of endocrine factors on bone remodelling is derived primarily from studies that have identified corresponding receptors expressed on osteoblasts and/or osteoclasts [ 31 ]. However, in vivo evidence showing a clear effect of these endocrine factors on bone metabolism is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic evidence explaining the involvement of endocrine factors on bone remodelling is derived primarily from studies that have identified corresponding receptors expressed on osteoblasts and/or osteoclasts [ 31 ]. However, in vivo evidence showing a clear effect of these endocrine factors on bone metabolism is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, equally diverse research paradigms support that dietary protein increases calcium absorption or bioavailability, 8–13 casting the net effect of high‐protein diets on the calcium economy into doubt. Furthermore, trials have persuasively demonstrated that increased protein intake may initiate bone anabolism mediated by the protein‐sensitive insulin‐like growth factor 1 (IGF‐1) 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, trials have persuasively demonstrated that increased protein intake may initiate bone anabolism mediated by the protein-sensitive insulin-like growth factor 1 (IGF-1). [14][15][16] In the midst of so many valid mechanisms for dietary protein to either enhance or degrade bone health, a recent meta-analysis 17 found no overall effect in observational studies, excepting a modest benefit to bone mineral density of the lumbar spine. However, even this effect was so small as to be of questionable clinical importance, casting doubt as to whether higher protein intakes influence bone at all.…”
Section: Introductionmentioning
confidence: 99%